Exercise behavior of ultramarathon runners: Baseline findings from the ULTRA Study - Hoffman, M. D.; Krishnan, E. (The Journal of Strength and Conditioning Research, 2013)
Little is known about exercise habits of those who compete in foot races longer than the standard 42-km marathon distance. The purpose of this work was to describe the past-year and lifetime exercise patterns of a large cohort of ultramarathon runners. Information on exercise history was collected on 1,345 current and former ultramarathon runners as baseline data for participation in a longitudinal observational study. Median age at the first ultramarathon was 36 years, and the median number of years of regular running before the first ultramarathon was 7 (interquartile range, 3-15). Age at first ultramarathon did not change across the past several decades, but there was evidence of an inverse relationship (r = -0.13, p < 0.0001) between number of years of regular running before the first ultramarathon and calendar year. The active ultramarathon runners (n = 1,212) had a previous year median running distance of 3,347 km, which was minimally related to age (r = -0.068, p = 0.018), but mostly related to their longest ultramarathon competition of the year (p < 0.0001). Running injuries represented the most common reason for discontinuation of regular running, whereas work and family commitments were reported as the main reasons for not running an ultramarathon in the previous year among those who were regularly running and intending to run ultramarathons again. We conclude that runners tend to be well into adulthood and with several years of running experience before running their first ultramarathon, but 25% have only been regularly running for 3 years or less at the time of their first ultramarathon.